2018
DOI: 10.3389/fmicb.2017.02701
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, pH, and Their Interaction Affect the Inhibitory Effects of Carvacrol against Salmonella Typhimurium PT4 and Escherichia coli O157:H7

Abstract: Although carvacrol (CAR) is considered an alternative antimicrobial for use in food, few is known about the influence of food-related parameters on its inhibitory effects against pathogens. This study assessed the influence of different amounts of proteins, using beef extract (BE) as a protein-rich source, lipids (LIP), using sunflower oil as a LIP-rich source, and pH values or their interaction on the inhibitory effects of CAR against Salmonella Typhimurium PT4 (ST) and Escherichia coli O157:H7 (EC). The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…In our case, it was observed that for Salmonella cocktails, the efficacy of oregano EO increased at a higher pH (6.5). A similar behavior was observed by Carvalho et al (2018), who reported that increasing pH values (6.0, as opposed to 5.0 or 5.5) in combination with an increase in lipids (6.25 ml/100 ml as opposed to 3.75 or 5.00 ml/100 ml) had a positive effect on the inhibitory effects of carvacrol against S . Typhimurium and E. coli .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In our case, it was observed that for Salmonella cocktails, the efficacy of oregano EO increased at a higher pH (6.5). A similar behavior was observed by Carvalho et al (2018), who reported that increasing pH values (6.0, as opposed to 5.0 or 5.5) in combination with an increase in lipids (6.25 ml/100 ml as opposed to 3.75 or 5.00 ml/100 ml) had a positive effect on the inhibitory effects of carvacrol against S . Typhimurium and E. coli .…”
Section: Resultssupporting
confidence: 86%
“…Even when EOs have been proven useful for the control of pathogenic bacteria in vitro, their effectiveness in food products may be hindered by the interaction of their constituents with food matrix components and/or physicochemical parameters (Boskovic et al, 2013; de Carvalho et al, 2015; Firouzi, Shekarforoush, Nazer, Borumand, & Jooyandeh, 2007; Gill, Delaquis, Russo, & Holley, 2002; Gutierrez, Barry‐Ryan, & Bourke, 2009; Hyldgaard et al, 2012; Tassou, Drosinos, & Nychas, 1995; Tserennadmid et al, 2010; Veldhuizen, Creutzberg, Burt, & Haagsman, 2007). In this viewpoint, food model media, where components and parameters can be controlled, are useful to investigate the interaction of EOs with given food components, and thus, give a quick assessment of the type of food products where an EO can be utilized (Carvalho, de Jesus Medeiros, Chaves, de Souza, & Magnani, 2018; Hyldgaard et al, 2012). Previous studies suggest that lipid concentrations above 5% will have strong effects on the effectiveness of essential oils or their components on bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common suggestion is that the increased fat content decreases the efficiency of EOs as they dissolve in fat, not affecting the bacteria that reside in the aqueous phase of food (Burt, 2004). This hypothesis has been supported by the results of several studies involving a laboratory medium with sunflower oil (Carvalho, de Jesus Medeiros, Chaves, de Souza, & Magnani, 2018; Gutierrez et al, 2008) and pork fat (García‐Díez et al, 2017), a comparison of low‐fat and high‐fat cheeses (Smith‐Palmer, Stewart, & Fyfe, 2001), fish (Mejlholm & Dalgaard, 2002) and hot dogs (Singh, Singh, Bhunia, & Singh, 2003). However, no complex study has been conducted to elucidate the extent to which the fat content decreases the antimicrobial effect of EOs in meat.…”
Section: Introductionmentioning
confidence: 57%
“…Our work confirmed a different degree of inhibition against tested strains. In 2018, a recent study supported this opinion describing that different physical, chemical factors, and their interaction influence the inhibitive effect of the natural antimicrobial compound against salmonella Typhimurium PT4 and E. coli O157:H7 (Carvalho et al 2018).…”
Section: Discussionmentioning
confidence: 91%